1997
DOI: 10.1074/jbc.272.8.4740
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of PKN with α-Actinin

Abstract: PKN is a fatty acid-and Rho-activated serine/threonine protein kinase, having a catalytic domain homologous to protein kinase C family. To identify components of the PKN-signaling pathway such as substrates and regulatory proteins of PKN, the yeast two-hybrid strategy was employed. Using the N-terminal region of PKN as a bait, cDNAs encoding actin cross-linking protein ␣-actinin, which lacked the N-terminal actin-binding domain, were isolated from human brain cDNA library. The responsible region for interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 46 publications
5
71
0
Order By: Relevance
“…C2-like domains might function as calcium-independent phospholipid binding domains but could also function as protein-protein interaction domains (22). PRK1 interacts with the actin filament binding protein ␣-actinin, and the interacting region has been mapped to residues 136 to 474, a region that overlaps with the C2-like domain (25). Interestingly, ␣-actinin localizes to adherens junctions in epithelial cells, raising the possibility that ␣-actinin recruits PRK2 to junctions (28).…”
Section: Discussionmentioning
confidence: 99%
“…C2-like domains might function as calcium-independent phospholipid binding domains but could also function as protein-protein interaction domains (22). PRK1 interacts with the actin filament binding protein ␣-actinin, and the interacting region has been mapped to residues 136 to 474, a region that overlaps with the C2-like domain (25). Interestingly, ␣-actinin localizes to adherens junctions in epithelial cells, raising the possibility that ␣-actinin recruits PRK2 to junctions (28).…”
Section: Discussionmentioning
confidence: 99%
“…Catalytically active PRK1/PKN has been reported to promote actin stress fibre disassembly, 58 possibly resulting from the phosphorylation of the actin binding protein a-actinin as well as the phosphorylation of monomeric actin. 59 A C-terminal fragment of PRK2 released by caspase-mediated proteolysis may feed forward to promote apoptosis by inhibiting the catalytic activity of the anti-apoptotic protein kinase Akt/PKB and reduce its inhibitory phosphorylation of the pro-apoptotic Bcl-2 family member Bad. 60 PAK isoforms also have been shown to lead to actin stress fibre disassembly, 23,61 ± 63 possibly through the phosphorylation of the myosin-II heavy chain, 64 which is thought to promote actin-myosin destabilisation, 65 and through the phosphorylation and consequent inhibition of the MLC kinase.…”
Section: Second Phase: Breakdown Of Actin Structures and Apoptotic Bomentioning
confidence: 99%
“…We previously demonstrated that PKN associates with and phosphorylates intermediate filament proteins in vitro (17,18), which may be physiological substrates for PKN. PKN interacts with the actin cross-linking protein ␣-actinin, but does not efficiently phosphorylate it in vitro (19), suggesting that ␣-actinin serves as a scaffolding protein that targets PKN to specific cytoskeletal substrates.…”
mentioning
confidence: 99%